1993
DOI: 10.1523/jneurosci.13-09-04042.1993
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of axotomized immature rat facial motoneurons by R(-)-deprenyl: stereospecificity and independence from monoamine oxidase inhibition

Abstract: The role of monoamine oxidase B (MAO-B) in R(-)-deprenyl-mediated rescue of rat facial motoneurons axotomized at postnatal day 14 (P14) was investigated using the (+)- and (-)-enantiomers of deprenyl [S(+)-deprenyl and R(-)-deprenyl]. Previously, doses of R(-)-deprenyl sufficient to inhibit MAO-B were shown to increase the survival of motoneurons following an apparent loss of target-derived trophic support caused by axotomy in P14 rats. In the present experiments, motoneuronal survival was measured 21 d after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(61 citation statements)
references
References 45 publications
5
55
1
Order By: Relevance
“…However, post-treatment selegiline reversed the shortening of the stride lengths. Moreover, this was not associated with other neurorescue mechanisms apart from MAO-B inhibition; the dose of selegiline (1.0 mg/kg/day) used in our study was lower than the dose reported to inhibit MAO (37). Furthermore, the delayed start of administration in our experiment ensured that any observed effects were not due to the compound interfering with the conversion of MPTP to its active metabolite, MPP + , a reaction that is mediated by MAO-B (15).…”
Section: Discussioncontrasting
confidence: 49%
“…However, post-treatment selegiline reversed the shortening of the stride lengths. Moreover, this was not associated with other neurorescue mechanisms apart from MAO-B inhibition; the dose of selegiline (1.0 mg/kg/day) used in our study was lower than the dose reported to inhibit MAO (37). Furthermore, the delayed start of administration in our experiment ensured that any observed effects were not due to the compound interfering with the conversion of MPTP to its active metabolite, MPP + , a reaction that is mediated by MAO-B (15).…”
Section: Discussioncontrasting
confidence: 49%
“…Ansari et al (1993) showed that selegiline rescued axotomized motoneurons independently of an inhibition of MAO-B. Other results have shown that the neurotrophic factors, such as basic fibroblast growth factor (bFGF; Grothe and Unsicker, 1992), brain-derived neurotrophin factor (BDNF; Yan et al, 1992), and ciliary neurotrophic factor (CNTF; Sendtner et al, 1992), reduce experimental axotomy-induced death of facial or hypoglossal motoneurons in neonatal or immature rats similarly to the reduction produced by selegiline.…”
Section: Selegiline Possesses Neurotrophic-like Action and Rescues Axmentioning
confidence: 97%
“…Thomas et al (1997) suggested that peroxyl radical trapping by l-deprenyl rather than ÂĄ OH trapping activity contributes to the therapeutic efficacy of MAO-B inhibitors. Results of studies using low doses of l-deprenyl (Ïœ0.01 mg/kg) after facial nerve transection suggest that its neuroprotective mechanism is independent of MAO-B inhibition (Ansari et al 1993). This notion is consistent with the finding that l-deprenyl protects against Author for correspondence: J. Jolkkonen, Department of Neuroscience and Neurology, University of Kuopio, PO Box 1627, FIN-70211 Kuopio, Finland (fax π358 17 162048, e-mail jukka.jolkkonen/uku.fi).…”
mentioning
confidence: 99%